Where to conserve? Plant biodiversity and endemism in mediterranean Mexico - Vanderplank, Sula E.; Rebman, Jon P.; Ezcurra, Exequiel (Biodiversity and conservation, 2018)
Six regions of northwestern (NW) Baja California (Sierra de Juárez, Sierra de San Pedro Mártir, Punta Banda, Colonet, San Quintín and Valle Tranquilo) were compared for their floristic diversity. Checklists for each region were analyzed by their total, native, and endemic floras to give measures of floristic similarity and overlap, and to identify the strongest gradients affecting species distributions. Each region was floristically distinct, with significant variation in the distribution of state endemic taxa. The six regions are readily differentiated by their geographical position in a Principal Components Analysis. The strongest gradients were (a) the W–E gradient from the coast to the mountains and (b) the latitudinal gradient from N to S. These six adjacent regions are found within a local and global biodiversity hotspot that is subject to intense conservation challenges. Conservation of many areas is essential to adequately preserve the diversity of locally endemic taxa with restricted ranges, yet the coast lacks any protected areas at the state and federal level. Private reserves such as Reserva Natural San Quintín may be critical to the conservation of regionally endemic taxa.